Experimental study on Titanium diamond by fabricating micro-holes using Micro-EDM with Taguchi's method and response surface method. (30th November 2020) - Sahoo, Rajesh; Kar, Siddhartha; Patowari, Promod Kumar
Abstract: Titanium alloys are very hard to machine materials, which can be machined effectively by using advanced manufacturing processes. Electro discharge machining (EDM) process is one of the most efficient methods of machining electrically conductive materials. EDM is focused more on the precision and accuracy of the machined parts. This particular work focuses on the machinability study of titanium diamond using micro-EDM. Input parameters such as voltage, capacitance, feed rate and tool rotation speed (TRS) are varied and their effects are analyzed by evaluating responses such as material removal rate (MRR), machining time (MT), overcut (OC) and circularity error (CE). X-ray diffraction (XRD) analysis of the material is also conducted to observe the material phases and elements. The observed responses are simultaneously optimized by formulating overall evaluation criteria (OEC) for generating the optimal value of process parameters. Further, the analysis of variance (ANOVA) provides the influence of input parameters on each output response. The variation of different response measures with respect to input parameters is shown through 3D response surface plots. It is observed in micro EDM that the MT decreases with the increase in voltage, capacitance, feed rate and TRS, whereas MRR and OC increase with an increase in voltage and capacitance. In the case of CE, it decreases with the increase in voltage and it increases with the increase in capacitance.